A first approach to reconstruct the production technology of Zsolnay ceramic panel paintings with oil painting effect. (June 2021) - Bajnóczi, Bernadett; Szabó, Máté; May, Zoltán; Rostás, Péter; Tóth, Mária
Highlights: Artistic paintings on large Zsolnay "pyrogranite" ceramic panels are studied. The King Béla IV painting employed two different technological methods. Coloured clay slips atop a white tin glaze were used to paint the portrait. Transparent lead glaze covers the coloured slips similarly to Renaissance maiolica. White glaze was covered by a blue glaze and a gold paint in the surrounding motifs. Abstract: Colourful and artistic ceramic panel paintings that realistically imitate oil paintings were one of the innovations of the Hungarian Zsolnay ceramic factory. Ten large ceramic panel paintings and two overdoor compositions (each containing three panels) decorated the Saint Stephen Hall in the palace of the Buda Castle (Budapest) established around the turn of the 19th and 20th centuries. However, the ceramic paintings were destroyed during World War II. In this study, three experimental Zsolnay panel paintings, as preparatory pieces for the original series, were examined to reconstruct the material usage and the production technology. Microanalytical investigation of the samples detached from one of the experimental panel paintings (portrait of King Béla IV) demonstrated that the panel, made of porous ceramic known as pyrogranite, was first covered by a white clay slip layer, and then by a primary white tin glaze layer, which served as a "ground" for the painting. The portrait of King Béla IV and the surrounding golden decorative motifs were created with different technologies. Coloured clay pastes (slips) were used to paint the portrait, which was then covered by a secondary transparent lead glaze, whereas a blue glaze covered by a thin layer of gold paint was applied over the primary glaze of the golden motifs. Non-destructive handheld XRF analysis revealed slight differences between the three experimental panel paintings, particularly in the tin content of the primary glaze layer and the colourants used, which were possibly related to the experimentation performed at the Zsolnay factory before the creation of the final paintings.